(untitled) (Research, Society and Development, 2020)
This article consists of the construction of an optical sensor prototype, for analysis of the physical-chemical quality of the oil used in transformers. For that, we used a range of oil samples, taken from different transformers, under different conditions, whose information was stored in a database that would allow them to be characterized in order to create a set of samples that portray the boundary conditions as much as possible. necessary to enable greater security in the sensing and use of optoelectronics. In order to obtain greater precision, long series of measurements were carried out, using more than 100 samples of mineral oil in just over 2,000 simulations, aiming to ensure the prototype met the metrics related to oil quality and greater accuracy to the study. The optical technique used for the development of the prototype was flowering, scanning the UV, Visible and IR regions in order to find the ideal light length for an accurate measurement and that met the technical standards and parameters already adopted and consolidated in this industry . For the purpose of analyzing the results, the techniques of FTIR, UV-VIS, fluorescence, mathematical methods were used, such as: coefficient of determination R2, partial regression of least squares, multiple minimums and Savitzky-Golay. The research proved, through simulations, different measures and prototyping of the hardware and software circuits, the feasible applicability of this implementation proposal, presenting a prototype of an optical sensor for measuring oil parameters for transformers.